Comparison of integrated genotoxicity endpoints in rats after acute and subchronic oral doses of 4‐nitroquinoline‐1‐oxide. (26th September 2015) - Roberts, Daniel J.; McKeon, Marie; Xu, Yong; Stankowski, Leon F.
Abstract : During interlaboratory validation trials for the Pig‐a gene mutation assay we assessed the genotoxicity of 4‐nitroquinoline‐1‐oxide (4NQO) across endpoints in multiple tissues: induction of Pig‐a mutant red blood cells (RBCs) and reticulocytes (RETs); micronucleated RETs (MN RETs); and DNA damage in blood and liver via the alkaline Comet assay (%tail intensity [TI]). In a previous subchronic toxicity study with 28 daily doses, biologically meaningful increases were observed only for Pig‐a mutant RBCs/RETs while marginal increases in the frequency of MN RET were observed, and other clastogenic endpoints were negative. Follow up acute studies were performed using the same cumulative doses (0, 35, 70, 105, and 140 mg/kg) administered in a bolus, or split over three equal daily doses, with samples collected up to 1 month after the last dose. Both of the acute dosing regimens produced similar results, in that endpoints were either positive or negative, regardless of 1 or 3 daily doses, but the three consecutive daily dose regimen yielded more potent responses in TI (in liver and blood) and Pig‐a mutant frequencies. In these acute studies the same cumulative doses of 4NQO induced positive responses in clastogenic endpoints that were negative or inconclusive using a subchronic study design. Additionally, a positive control group using combination doses of cyclophosphamide and ethyl methanesulfonate was employed to assess assay validity and potentially identify a future positive control treatment for integrated genetic toxicity studies. Environ. Mol. Mutagen. 57:17–27, 2016. © 2015 Wiley Periodicals, Inc.